2020
DOI: 10.29252/payesh.19.3.255
|View full text |Cite
|
Sign up to set email alerts
|

Equity in hospital beds distribution in Zanjan Province, Iran

Abstract: Health equity as a health system objective means having fair access to needed healthcare services, paying healthcare costs according to payment capacity and enjoying the highest achievable standard of health. Equitable distribution of hospital beds increases people access to health services and as a result improves their health status. This study aimed to examine the equity in distribution of hospital beds in Zanjan Province, Iran. Methods: Data for this descriptive and cross sectional study was collected from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Accumulation of more hospital beds in the center of the province and more developed cities with better living conditions and higher income will lead to more concentration of hospital workers such as doctors and nurses in these cities and It will have a negative effect on people's health (increasing medical errors, unnecessary admissions, hospital infections, etc.) in less privileged cities [ 40 ]. Of course, due to the limited number of studies, this finding should be interpreted with caution, and further research in different provinces of the country is needed for effective evaluation and planning.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulation of more hospital beds in the center of the province and more developed cities with better living conditions and higher income will lead to more concentration of hospital workers such as doctors and nurses in these cities and It will have a negative effect on people's health (increasing medical errors, unnecessary admissions, hospital infections, etc.) in less privileged cities [ 40 ]. Of course, due to the limited number of studies, this finding should be interpreted with caution, and further research in different provinces of the country is needed for effective evaluation and planning.…”
Section: Discussionmentioning
confidence: 99%
“…In Iran, despite many developments in the country's healthcare system, there are still many challenges related to inequality in the distribution of resources (Shamsi et al, 2014). Many studies have been conducted nationwide, which show that the distribution of hospital beds is unfair in some provinces (Mojiri & Ahmadi, 2022; Mosadeghrad, Dehanavi, et al, 2020). The study by Mosadeghrad, Dehanavi, et al (2020) showed that hospital beds are mainly concentrated in provincial centers and not fairly distributed in other cities.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been conducted nationwide, which show that the distribution of hospital beds is unfair in some provinces (Mojiri & Ahmadi, 2022; Mosadeghrad, Dehanavi, et al, 2020). The study by Mosadeghrad, Dehanavi, et al (2020) showed that hospital beds are mainly concentrated in provincial centers and not fairly distributed in other cities. Furthermore, the mentioned study showed that most of the hospital beds were located in central Iran and near Tehran province, so that about 22% of the hospital beds were concentrated in the country's capital (Mosadeghrad, Janbabaei, et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…One of the appropriate social institutions for realizing a healthy and active society is the school. Schools are the most important social element influencing the formation of beliefs, personalities, and lifestyles, which deals with the most sensitive age group of any society and is the product of human culture's efforts to survive education (Mosadeghrad et al, 2020).…”
Section: Introductionmentioning
confidence: 99%